Comparative analysis of methods of training and dietary habits of skilled bodybuilders in the run-general preparatory stage - V.Y. Dzhym (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : comparative analysis of the characteristics of methods of training and nutrition bodybuilders in the run-general of the preparatory phase (duration 4 - 5 months or 20 microcycles). Analyzed the characteristics of different methods of training bodybuilders to increase muscle mass. Material : the study involved 8 skilled bodybuilders, are included in the team of the Kharkiv region. Results : a comparative characteristic of the most commonly used methods of exercise and nutrition in bodybuilding. Discovered and proved the optimal technique for athletes depending on the original form at the beginning of general-preparatory phase of training. Driven changes in body weight, depending on the amount used Athlete of carbohydrates, proteins and fats. Conclusions : throughout the training period was characterized by severe protein diet orientation. The proportion of the nutrient was 40% in the first quarter, 50% - in the second, 60% in the third. Only in the last two microcycle decreased to 50%.